Reviews in computational chemistry. - Lipkowitz, Kenny B.; Boyd, Donald B. (Reviews in Computational Chemistry., 2002)
This volume, like those prior to it, features chapters by experts in various fields of computational chemistry. Topics covered in Volume 18 include molecular modeling, computer-assisted molecular design (CAMD), quantum chemistry, molecular mechanics and dynamics, and quantitative structure-activity relationships (QSAR).